Impact of Fuel Subsidy Removal on Trading and Marketing Activities in Takum LGA of Taraba State, Nigeria - Shipurut, Geoffrey Nanbal; Onyedikachi, Nwanma Gloria; Abubakar, Ali (Darul Yasin Al Sys, 2025)
The removal of fuel subsidies led to a rise in the price of fuel. These rapid changes hurt the activities of many Nigerians as nearly all homes and businesses use subsidised petrol to power their generators due to the problems with the nation's electrical supply. This paper looks into the impact of fuel subsidy removal on trading/marketing activities in Takum LGA. The study used a descriptive, cross-sectional survey research design. A sample size of 400 respondents was selected from the total population of 211,700 using the Tare Yamane formula. Questionnaires were distributed to 400 respondents who were randomly selected across the wards in Takum LGA. Responses from the questionnaire were analysed using the descriptive statistics of frequency counts and percentages, and Pearson Correlation. The Pearson Correlation was used to test the stated hypotheses at a 0.05 level of significance with the use of SPSS (Statistical Package for Social Sciences). The study revealed that the removal of petroleum subsidies had its most severe impact on trading and marketing activities during May–August 2023, as businesses were unprepared for the sudden fuel price spike, leading to disrupted supply chains and reduced profits. Although the impact slightly moderated in September–December 2023, it persisted into January–March 2024, indicating prolonged economic stress. The study recommended that a targeted measure, like financial assistance for small firms, transportation subsidies for necessities, and infrastructure investments to stabilise supply chains, should be implemented with subsidy removal policies.